Motivational Influences and Trajectories to Violence in the Context of Major Mental Illness - Penney, Stephanie R. (Journal of interpersonal violence, 2021)
Developmental trajectories regarding the age onset of violence and offending have not routinely considered the role of major mental illness (MMI). In parallel, despite several studies investigating the relationship between MMI, violence and offending, fewer have identified motivational processes that may link illness to these outcomes in a more direct and proximal manner. This study investigates whether subtypes of forensic psychiatric patients deemed Not Criminally Responsible on account of Mental Disorder (N = 91) can be identified based on the age onset of mental illness and offending behavior, and whether information on motivational influences for offending—elicited both from the patient directly and detailed collateral information—contributes to the clinical utility of this typology. Results indicated that most patients reported engaging in violence (51%) or antisocial behaviors (72%) prior to the onset of MMI, but that the index offense(s) resulting in forensic admission were predominantly psychotically motivated. In contrast to patients for whom the onset of MMI occurred prior to offending, patients exhibiting premorbid violence had higher levels of risk and criminogenic need; they were more likely to be diagnosed with personality and substance use disorders, and to have conventional (i.e., non-illness-related) motivations ascribed to their index offense. Findings are consistent with the existing literature regarding subgroups of mentally disordered offenders, but provide new information regarding proximal risk factors for violence through better identification of motivational processes.